Gambaran Denver Development Screening Test (DDST) dan Kuesioner Pra Perkembangan (KPSP) Anak Usia Pra Sekolah Domisili di Jepang - Rani, Puspa; Eka Rokhmiati; Irma Herliana (2025)
Early childhood development is crucial to prevent developmental delays in preschool-aged children. Therefore, early detection is essential to identify any developmental disorders as early as possible. This can be achieved using screening instruments such as the Denver Developmental Screening Test (DDST) and the Pre-Screening Developmental Questionnaire (KPSP). This study aims to describe the developmental assessment results of preschool children residing in Japan using both DDST and KPSP methods. This research is an observational study with a cross-sectional approach and employs a descriptive survey design. The study was conducted from May to June 2024, involving 25 preschool-aged children selected using a total sampling technique. The independent variables in this study are the screening methods (KPSP and DDST), while the dependent variable is the developmental status of the children. Data were collected through measurements of body weight, height, and head circumference, as well as the completion of the KPSP form and DDST chart. Univariate analysis was performed to describe each variable using frequency distribution in percentage form. The results showed that most respondents were 66 months old (56%), with the lowest frequency being 72 months old (8%). Most children were categorized as